Identifying and alleviating pain associated with routine husbandry procedures performed on pre and post weaning dairy calves - Glynn, Hayley Deanna (Kansas State University, 2012)
This thesis includes two studies that assessed pain responses to husbandry procedures in order develop mitigation tools. The objective of the first trial was to identify method-related differences in behavioral pain responses in calves of two ages (6 week and 6 months) subjected to castration: surgical cut (CP; n=18), surgical cut and emasculator (CC; n=20), rubber banding (BAND; n=18), or control manipulation of the scrotum (CONT; n=20). Behavior was evaluated pre- and post-castration to record foot stamps, tail flicks, kicks, elimination, in addition to standing and lying post-castration. For 6 week calves, the probability of kicking and eliminations was greater for surgical castrates and all castrated animals, respectively. The probability of kicking was greatest for all 6 month castrates while BAND and CONT had greater probability of elimination. Both age groups increased standing post-castration. Lying decreased in 6 week calves but was unchanged for 6 month calves. Six week calves displayed more tail flicks and tended to display less foot stamps than 6 month calves. Six week calves showed a decrease in tail flicks and foot stamps in response to castration while 6 month calves showed an increase in both behaviors. CP and CC, but not BAND, resulted in less tail flicks than CONT post castration. The second trial compared the effects of preemptive analgesics administered to calves subjected to dehorning with local anesthesia. Six month Holstein steers were randomly assigned to receive one of the following treatments (n= 8/group): meloxicam (1 mg/kg PO), gabapentin (15mg/kg PO), meloxicam (1 mg/kg) and gabapentin (15 mg/kg) PO, flunixin (2.2 mg/kg IV), or a placebo. Drug, cortisol, ex-vivo prostaglandin, haptoglobin, and substance P concentrations, ocular thermography, algometry, and average daily gain were evaluated. Analgesic-treated calves had lower plasma SP concentrations and improved ADG compared with controls. Flunixin calves had reduced cortisol and ex-vivo prostaglandin concentrations for 24h compared to controls. Meloxicam treated calves showed an increase in MNT at two horn bud sites compared with the other treatments. Overall, the results provide validation of responses to noxious stimuli that can be used to develop pain alleviation for livestock.
Keywords: Calves; Pain; Behavior; Castration; Dehorning; Pain alleviation; Animal Sciences (0475); Biology, Animal Physiology (0433)